Method for rapidly detecting whether color paste is thickened after being stored

By measuring the curve of the viscosity of the color paste with the shear rate in the rheometer and calculating the enclosed area, it quickly judges whether the color paste has thickening problems after storage, which solves the problem of long detection cycles in the prior art, and significantly improves the efficiency of color paste development.

CN119643370APending Publication Date: 2025-03-18NIPPON PAINT CHINA +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311199362.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing methods to detect whether the color paste thickens after storage have a long cycle, resulting in a long development time for the color paste formula and low efficiency.

Method used

By cooling the color paste to be measured to room temperature after being stored by heat, and applying shear force in the rheometer, measuring the curve of viscosity with shear rate, and calculating the part of the area enclosed by the curve, and determining whether there is a problem of thickening after storage of the color paste.

Benefits of technology

This method can quickly judge and predict the degree of thickening of color paste after storage, shorten the detection cycle, from more than 4 weeks to less than 3 days, and significantly improve the efficiency of color paste development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643370A_ABST
    Figure CN119643370A_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly detecting whether color paste is thickened after being stored. The method comprises the following steps: thermally storing the color paste to be detected, and cooling to room temperature; applying a shearing force to the to-be-measured color paste, increasing the shearing rate from the initial shearing rate to the set shearing rate at a constant speed, measuring the viscosity of the to-be-measured color paste at different shearing rates in the process to obtain a change curve of the viscosity along with the shearing rate, and recording the change curve as a curve S1; uniformly reducing the shearing rate from the set shearing rate to the initial shearing rate, measuring the viscosity of the to-be-measured color paste at different shearing rates in the process to obtain a change curve of the viscosity along with the shearing rate, and recording the change curve as a curve S2; and calculating the area of a part enclosed by the curve S1 and the curve S2, and judging whether the color paste to be detected is thickened after being stored according to the area. The method can well solve the problem that an existing method for detecting whether the color paste is thickened or not after being stored is long in period.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of pigment paste, and more specifically, to a method for quickly detecting whether the paste thickens after storage. Background Art

[0002] As a coloring material, color paste can not only make the paint present rich and colorful colors, but also give the paint better hiding power, mechanical strength and other properties. It is an indispensable component of the paint. During the storage of color paste, the problem of thickening after storage is often encountered. On the one hand, thickening after storage will reduce the fluidity of the color paste, thereby reducing the use efficiency and color matching accuracy of the color paste; on the other hand, thickening after storage may also cause the pigment particles in the color paste to flocculate, resulting in changes in the color and tinting strength of the color paste and making it unusable. Therefore, in the color paste formula development stage, the problem of thickening of the color paste after storage needs to be fully considered.

[0003] At present, the method for detecting the thickening of color paste after storage mainly relies on the thermal storage acceleration method, that is, the color paste is first stored in a certain temperature atmosphere for 4 weeks, and then the Stormer viscosity or Brookfield viscosity is tested, combined with visual observation to determine the thickening of the color paste after storage. If the color paste thickens severely after storage, the formula needs to be adjusted and the storage experiment needs to be repeated. In this way, each test cycle takes more than 4 weeks, resulting in a long time and low efficiency in the development of the color paste formula. Summary of the invention

[0004] Based on the above reasons, the purpose of the present invention is to provide a method for quickly detecting whether the color paste thickens after storage, so as to solve the problem that the existing method for detecting whether the color paste thickens after storage has a long cycle.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for quickly detecting whether a color paste thickens after storage, characterized in that it comprises the following steps:

[0007] Cool the color paste to be tested to room temperature after hot storage;

[0008] Applying shear force to the color paste to be tested and uniformly increasing the shear rate from the initial shear rate to the set shear rate, measuring the viscosity of the color paste to be tested at different shear rates during this process, and obtaining a curve of viscosity versus shear rate, which is recorded as curve S1;

[0009] The shear rate is uniformly reduced from the set shear rate to the initial shear rate, and the viscosity of the color paste to be tested at different shear rates is measured during this process to obtain a curve of viscosity versus shear rate, which is recorded as curve S2;

[0010] The area of ​​the portion enclosed by the curve S1 and the curve S2 is calculated, and based on this, it is determined whether the color paste to be tested has thickened after storage.

[0011] Furthermore, the heat storage temperature is 40-60°C and the time is 18-48h.

[0012] Furthermore, the condition of cooling to room temperature includes: placing the color paste to be tested after heat storage at a constant temperature of 23° C. for 6-10 hours.

[0013] Furthermore, the initial shear rate is 0.005s -1 -0.02s -1 , set the shear rate to 90s -1 -110s -1 .

[0014] Furthermore, the total time for the uniform increase and decrease of the shear rate is 80-120 s, and the viscosity of the color paste to be tested is measured by sampling every 5 s.

[0015] Further, the method for determining whether the color paste to be tested has thickened after storage is:

[0016] If the area is less than 20000 mPa, the color paste to be tested has no problem of thickening after storage;

[0017] If the area is above 20,000 mPa, the color paste to be tested has a problem of thickening after storage.

[0018] Furthermore, if the area is between 20000-40000 mPa, the color paste to be tested has a slight thickening problem after storage; if the hysteresis loop area is greater than 40000 mPa, the degree of thickening of the color paste to be tested after storage is more serious.

[0019] Furthermore, the color paste is a water-based color paste or a solvent-based color paste.

[0020] The beneficial effects of the present invention are as follows:

[0021] The method provided by the present invention can quickly judge and predict the degree of thickening of the color paste after storage, further improve the color paste development efficiency, shorten the test detection cycle from more than 4 weeks to less than 3 days, greatly improve the color paste development efficiency, and solve the problem of long color paste development cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0023] Figure 1 The rheological test curves and hysteresis loop schematic diagrams of color pastes in some embodiments of the present invention are shown. DETAILED DESCRIPTION

[0024] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0025] According to a specific embodiment of the present invention, a method for quickly detecting whether a color paste thickens after storage is provided, the method comprising the following steps:

[0026] 1) Cool the color paste to room temperature after hot storage.

[0027] Exemplarily, in this step, the temperature of the heat storage is 40-60°C and the time is 18-48 hours. Through heat storage, the aging of the color paste can be accelerated and the thickening cycle after the evaluation of the color paste can be reduced. The specific time of heat storage can be selected according to actual conditions, for example, 24-48 hours.

[0028] Exemplarily, the cooling condition to room temperature is: placing the color paste to be tested at a constant temperature of 23° C. for 6-10 hours, preferably 6-8 hours after heat storage. The rheological properties of the color paste will change with temperature, and the purpose of placing it at a constant temperature is to standardize the test process and improve the accuracy and repeatability of the method.

[0029] In this embodiment, the color paste to be tested may be a color paste required for use in the coating field, for example, architectural coatings, industrial coatings, automotive coatings, and the like.

[0030] 2) applying shear force to the color paste to be tested and uniformly increasing the shear rate from the initial shear rate to the set shear rate, measuring the viscosity of the color paste to be tested at different shear rates during this process, and obtaining a curve of viscosity versus shear rate, which is recorded as curve S1.

[0031] In this step, the shear force is applied to the color paste to be tested by placing the color paste to be tested in a rheometer and performing a rheological test using the rheometer.

[0032] For example, the abscissa of the curve S1 is the shear rate (s -1 ), the ordinate is viscosity (mPa·s).

[0033] In some examples, the initial shear rate is 0.005 s -1 -0.02s -1 , set the shear rate to 90s -1 -110s -1 In the specific implementation of the present invention, it is found that controlling the initial shear rate and the set shear rate within this range makes the detection method more accurate and rapid.

[0034] In some examples, the total time for the uniform increase in shear rate is 100 seconds, and the viscosity of the color paste to be tested is measured by sampling every 5 seconds. Under this condition, the detection method is more accurate and rapid.

[0035] 3) The shear rate is uniformly reduced from the set shear rate to the initial shear rate, and the viscosity of the color paste to be tested at different shear rates is measured during this process to obtain a curve of viscosity versus shear rate, which is recorded as curve S2.

[0036] On the basis of step 2), the rheometer test is continued to be performed to reduce the shear rate. The shear rate is uniformly reduced from the set shear rate in step 2) to the initial shear rate.

[0037] For example, the abscissa of the curve S2 is the shear rate (s -1 ), the ordinate is viscosity (mPa·s).

[0038] In some examples, the total time for the uniform reduction of the shear rate is 80-120 seconds, and the viscosity of the color paste to be tested is measured by sampling every 5 seconds. Under this condition, the detection method is more accurate and rapid.

[0039] In the above steps 2) and 3), the test temperature is preferably 23°C.

[0040] 4) Calculate the area of ​​the portion enclosed by the curve S1 and the curve S2, and use this area to determine whether the color paste to be tested has thickened after storage.

[0041] It can be understood that the curve S1 and the curve S2 have the same coordinate point at the set shear rate on the horizontal coordinate, that is, they overlap. Calculating the area of ​​the portion enclosed by the two curves is to calculate the area of ​​the portion enclosed by the two curves between the starting shear rate and the set shear rate on the horizontal coordinate. The area can be calculated according to the method of integrating the curve in mathematics, which will not be repeated here.

[0042] In some examples, specifically, the method for determining whether the color paste to be tested thickens after storage is:

[0043] If the area is less than 20000 mPa, the color paste to be tested has no problem of thickening after storage;

[0044] If the area is above 20,000 mPa, the color paste to be tested has a problem of thickening after storage.

[0045] By using this method and controlling the size of the enclosed area, the determination result is more accurate.

[0046] In some examples, if the area is between 20000-40000 mPa, the color paste to be tested has a slight thickening problem after storage; if the hysteresis loop area is greater than 40000 mPa, the degree of thickening of the color paste to be tested after storage is more serious. Through this method, the degree of thickening of the color paste to be tested can be accurately determined.

[0047] The technical solution of the present invention is described below in conjunction with some specific embodiments:

[0048] In a specific embodiment, the specific process of the experiment for detecting the thickening of the color paste after storage includes the following steps:

[0049] (1) Preparation of color paste samples:

[0050] Add dispersant, grinding resin, wetting agent and defoamer into part of the dispersion medium according to the formula weight, and stir at a speed of 800-1000 r / min for 10-20 min to obtain mixture A;

[0051] Then, adding anti-settling agent and pigment to mixture A, and dispersing at a speed of 1500-2000 r / min for 30 min to obtain mixture B;

[0052] Next, the mixture B is sand-milled and kept in the grinding state until the material fineness is dispersed to less than 10 μm, thereby obtaining a mixture C;

[0053] Finally, the fungicide and the remaining dispersion medium were added to the mixture C, and the mixture was stirred at a speed of 800-1000 r / min for 10 min to obtain a color paste sample.

[0054] (2) Color paste sample processing:

[0055] After the color paste to be tested is stored at 40-60°C for 18-48 hours, the color paste is taken out and placed in a constant temperature room at 23°C for 6-10 hours to cool the color paste to room temperature.

[0056] (3) Rheological test of color paste samples:

[0057] Place the cooled color paste sample on the rheometer to test the viscosity curve of the color paste sample with shear rate. The overall test temperature is 23°C. The rheological test mode is selected as the two-stage "Flow Curve: Measurement of viscosity by setting shear rate, Ramping log". The first stage program is: from the shear rate of 0.005s -1 -0.02s -1 To shear rate 90s -1 -110s -1, take a point every 5 seconds, and take 20 points in total; the second program is: from the shear rate 90s -1 -110s -1 To shear rate 0.005s -1 -0.02s -1 , take a point every 5 seconds, and take 20 points in total.

[0058] (4) Calculation of hysteresis loop area:

[0059] Using the calculation software, first integrate the curve obtained by the first program to obtain area A1, then integrate the curve obtained by the second program to obtain area A2, and through the mathematical calculation of A1-A2, the area of ​​the hysteresis loop is obtained. The curves obtained by each program and the schematic diagram of the hysteresis loop are shown in Figure 1 shown.

[0060] (5) Determination of thickening of color paste after storage:

[0061] The criteria for judging the degree of thickening of the color paste after storage are:

[0062] For pigment paste, if the hysteresis loop area is less than 20,000 mPa, the paste will not have the problem of thickening after storage;

[0063] If the hysteresis loop area is between 20,000 and 40,000 mPa, the color paste has a slight thickening problem after storage;

[0064] If the hysteresis loop area is greater than 40,000 mPa, the color paste thickens more severely after storage.

[0065] Example 1

[0066] Thickening test of water-based iron yellow paste after storage:

[0067] A series of water-based iron yellow slurries were prepared according to the formula in Table 1 below, including the following steps:

[0068] (1) Add the dispersant, wetting agent and defoaming agent into deionized water (deionized water 1) according to the formula weight, and stir at a speed of 800-1000 r / min for 10-20 min to obtain a mixture A.

[0069] (2) Add an anti-settling agent and iron yellow pigment to mixture A, and disperse at a speed of 1500-2000 r / min for 30 min to obtain mixture B.

[0070] (3) Grinding the mixture B, and maintaining the grinding state until the material fineness is dispersed to less than 10 μm, to obtain a mixture C.

[0071] (4) Add the fungicide and the remaining deionized water (deionized water 2) to the mixture C, and stir at a speed of 800-1000 r / min for 10 min to obtain an aqueous iron yellow slurry sample.

[0072] Table 1 Experimental formula of water-based iron yellow paste (the amount of each component is in parts by mass)

[0073]

[0074] A method for quickly detecting whether a color paste thickens after storage comprises the following steps:

[0075] After the prepared color paste is heat-stored at 50°C for 36 hours, the color paste is taken out and placed in a constant temperature room at 23°C for 8 hours to cool the color paste to room temperature;

[0076] Place the cooled color paste sample on the rheometer, set the test temperature to 23°C, and test the viscosity curve of the color paste sample as a function of shear rate. The rheological test mode is selected as the two-stage "Flow Curve: Measurement of viscosity by setting shear rate, Ramping log". The first stage of the program is: from the shear rate of 0.01s -1 To shear rate 100s -1 , take a point every 5 seconds, and take 20 points in total; the second program is: from the shear rate 100s -1 To shear rate 0.01s -1 , take a point every 5 seconds, and take 20 points in total;

[0077] Using the calculation software, the curve obtained by the first procedure is integrated to obtain the area A1, and then the curve obtained by the second procedure is integrated to obtain the area A2. The area of ​​the hysteresis loop is obtained by mathematical calculation of A1-A2. The initial viscosity and initial fluidity score of the color paste and the area of ​​the hysteresis loop obtained by the above method are shown in Table 2.

[0078] At the same time, the above-mentioned water-based iron yellow pastes were also aged at 50°C for 4 weeks to test the fluidity and viscosity of the paste before and after the hot storage. The test results are shown in Table 2.

[0079] Among them, the liquidity score reference data: 1. Completely illiquid, 2. Very poor liquidity, 3. Good liquidity, 4. Very good liquidity.

[0080] Table 2 Test results of water-based iron yellow paste

[0081]

[0082] According to the results in Table 2, it can be judged that the hysteresis loop area of ​​formulas 1 and 2 is less than 20000 mPa, the fluidity is very good after 4 weeks of hot storage, and there is no thickening problem after storage; the hysteresis loop area of ​​formulas 3 and 4 is between 20000-40000 mPa, the fluidity decreases slightly after 4 weeks of hot storage, and slight post-thickening occurs during storage; the hysteresis loop area of ​​formulas 5 and 6 is greater than 40000 mPa, the fluidity is very poor after 4 weeks of hot storage, and the thickening problem after storage is serious.

[0083] As can be seen from the above, the method of this embodiment is consistent with the conventional method of judging by hot storage for 4 weeks, which means that this method can quickly and accurately judge and predict the degree of thickening of the color paste after storage.

[0084] Example 2

[0085] Thickening test of water-based phthalocyanine green slurry after storage:

[0086] A series of water-based phthalocyanine green slurries were prepared according to the formula in Table 3 below, including the following steps:

[0087] (1) Add the dispersant, wetting agent and defoaming agent into deionized water (deionized water 1) according to the formula weight, and stir at a speed of 800-1000 r / min for 10-20 min to obtain a mixture A.

[0088] (2) Phthalocyanine green pigment was added to mixture A, and the mixture was dispersed at a speed of 1500-2000 r / min for 30 min to obtain mixture B.

[0089] (3) Grinding the mixture B, and maintaining the grinding state until the material fineness is dispersed to less than 10 μm, to obtain a mixture C.

[0090] (4) Add the fungicide and the remaining deionized water (deionized water 2) to the mixture C, and stir at a speed of 800-1000 r / min for 10 min to obtain an aqueous phthalocyanine green slurry sample.

[0091] Table 3 Experimental formula of water-based phthalocyanine green slurry (the amount of each component is in parts by mass)

[0092]

[0093] A method for quickly detecting whether a color paste thickens after storage comprises the following steps:

[0094] After the prepared color paste is heat-stored at 50°C for 36 hours, the color paste is taken out and placed in a constant temperature room at 23°C for 8 hours to cool the color paste to room temperature;

[0095] Place the cooled color paste sample on the rheometer, set the test temperature to 23°C, and test the viscosity curve of the color paste sample as a function of shear rate. The rheological test mode is selected as the two-stage "Flow Curve: Measurement of viscosity by setting shear rate, Ramping log". The first stage of the program is: from the shear rate of 0.01s -1 To shear rate 100s -1 , take a point every 5 seconds, and take 20 points in total; the second program is: from the shear rate 100s -1 To shear rate 0.01s -1 , take a point every 5 seconds, and take 20 points in total;

[0096] Using the calculation software, the curve obtained by the first procedure is integrated to obtain the area A1, and then the curve obtained by the second procedure is integrated to obtain the area A2. The area of ​​the hysteresis loop is obtained by mathematical calculation of A1-A2. The initial viscosity and initial fluidity score of the color paste and the area of ​​the hysteresis loop obtained by the above method are shown in Table 4.

[0097] At the same time, the above-mentioned water-based phthalocyanine green pastes were also aged at 50° C. for 4 weeks to test the fluidity and viscosity of the paste before and after the hot storage. The test results are shown in Table 4.

[0098] Reference data for liquidity score: 1. Totally illiquid, 2. Very poor liquidity, 3. Good liquidity, 4. Very good liquidity.

[0099] Table 4 Test results of water-based phthalocyanine green slurry

[0100]

[0101] According to the results in Table 4, it can be judged that the hysteresis loop area of ​​formulas 1-3 is greater than 40000 mPa, the fluidity is very poor after 4 weeks of hot storage, and the thickening problem after storage is serious; the hysteresis loop area of ​​formula 4 is between 20000-40000 mPa, the fluidity decreases slightly after 4 weeks of hot storage, and slight post-thickening occurs during storage; the hysteresis loop area of ​​formulas 5 and 6 is less than 20000 mPa, the fluidity is very good after 4 weeks of hot storage, and there is no thickening problem after storage.

[0102] As can be seen from the above, the method of this embodiment is consistent with the conventional method of judging by hot storage for 4 weeks, which means that this method can quickly and accurately judge and predict the degree of thickening of the color paste after storage.

[0103] Example 3

[0104] Thickening test of solvent-based phthalocyanine blue paste after storage

[0105] A series of solvent-based phthalocyanine blue slurries were prepared according to the formula in Table 5 below, including the following steps:

[0106] (1) adding the ground resin and the dispersant according to the formula weight into butyl acetate solvent (butyl acetate solvent 1), stirring at a speed of 800-1000 r / min for 10-20 min to obtain a mixture A;

[0107] (2) adding phthalocyanine blue pigment to mixture A and dispersing at a speed of 1500-2000 r / min for 30 min to obtain mixture B;

[0108] (3) sand-grinding the mixture B, and maintaining the grinding state until the material fineness is dispersed to less than 10 μm, to obtain a mixture C;

[0109] (4) Add the remaining butyl acetate solvent (butyl acetate solvent 2) to the mixture C, and stir at a speed of 800-1000 r / min for 10 min to obtain a solvent-based phthalocyanine blue slurry sample.

[0110] Table 5 Experimental formula of solvent-based phthalocyanine blue paste (amount of each component is in parts by mass)

[0111]

[0112] A method for quickly detecting whether a color paste thickens after storage comprises the following steps:

[0113] After the prepared color paste is heat-stored at 50°C for 36 hours, the color paste is taken out and placed in a constant temperature room at 23°C for 8 hours to cool the color paste to room temperature;

[0114] Place the cooled color paste sample on the rheometer, set the test temperature to 23°C, and test the viscosity curve of the color paste sample as a function of shear rate. The rheological test mode is selected as the two-stage "Flow Curve: Measurement of viscosity by setting shear rate, Ramping log". The first stage of the program is: from the shear rate of 0.01s -1 To shear rate 100s -1 , take a point every 5 seconds, and take 20 points in total; the second program is: from the shear rate 100s -1 To shear rate 0.01s -1 , take a point every 5 seconds, and take 20 points in total;

[0115] Using the calculation software, the curve obtained by the first procedure is integrated to obtain the area A1, and then the curve obtained by the second procedure is integrated to obtain the area A2. The area of ​​the hysteresis loop is obtained by mathematical calculation of A1-A2. The initial viscosity and initial fluidity score of the color paste and the area of ​​the hysteresis loop obtained by the above method are shown in Table 6.

[0116] At the same time, the above-mentioned solvent-based phthalocyanine blue pastes were also aged by heat storage at 50°C for 4 weeks, and the fluidity and viscosity of the pastes before and after heat storage were tested. The test results are shown in Table 6.

[0117] Reference data for liquidity score: 1. Totally illiquid, 2. Very poor liquidity, 3. Good liquidity, 4. Very good liquidity.

[0118] Table 6 Solvent-based phthalocyanine blue paste test results

[0119]

[0120] According to the results in Table 6, the hysteresis loop area of ​​formula 1 and 2 is less than 20000 mPa, and the fluidity is very good after 4 weeks of hot storage, and there is no thickening problem after storage; the hysteresis loop area of ​​formula 3 and 4 is greater than 40000 mPa, and the fluidity is very poor after 4 weeks of hot storage, and the thickening problem after storage is serious. Combined with the viscosity change before and after storage, it can be seen that this method can quickly determine and predict the degree of thickening of the color paste after storage.

[0121] As can be seen from the above, the method of this embodiment is consistent with the conventional method of judging by hot storage for 4 weeks, which means that this method can quickly and accurately judge and predict the degree of thickening of the color paste after storage.

[0122] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for quickly detecting whether a color paste thickens after storage, characterized in that: The steps include: Cool the color paste to be tested to room temperature after hot storage; Applying shear force to the color paste to be tested and uniformly increasing the shear rate from the initial shear rate to the set shear rate, measuring the viscosity of the color paste to be tested at different shear rates during this process, and obtaining a curve of viscosity versus shear rate, which is recorded as curve S1; The shear rate is uniformly reduced from the set shear rate to the initial shear rate, and the viscosity of the color paste to be tested at different shear rates is measured during this process to obtain a curve of viscosity versus shear rate, which is recorded as curve S2; The area of ​​the portion enclosed by the curve S1 and the curve S2 is calculated, and based on this, it is determined whether the color paste to be tested has thickened after storage.

2. The method according to claim 1, characterized in that The heat storage temperature is 40-60° C. and the time is 18-48 hours.

3. The method according to claim 1, characterized in that The condition of cooling to room temperature includes: placing the color paste to be tested after heat storage at a constant temperature of 23° C. for 6-10 hours.

4. The method according to claim 1, characterized in that: The initial shear rate is 0.005s -1 -0.02s -1 , set the shear rate to 90s -1 -110s -1 .

5. The method according to claim 4, characterized in that The total time for the uniform increase and decrease of the shear rate is 80-120 s, and the viscosity of the color paste to be tested is measured by sampling every 5 s.

6. The method according to claim 1, characterized in that The method for judging whether the color paste to be tested has thickened after storage is: If the area is less than 20000 mPa, the color paste to be tested has no problem of thickening after storage; If the area is above 20,000 mPa, the color paste to be tested has a problem of thickening after storage.

7. The method according to claim 6, characterized in that If the area is between 20000-40000 mPa, the color paste to be tested has a slight thickening problem after storage; if the hysteresis loop area is greater than 40000 mPa, the degree of thickening of the color paste to be tested after storage is more serious.

8. The method according to claim 1, characterized in that The color paste is a water-based color paste or a solvent-based color paste.